Cyclic Swell–Shrink Behavior of an Expansive Soil Treated with a Sulfonated Oil. Issue 1 (24th February 2020) - Soltani, Amin; Raeesi, Ramin; O'Kelly, Brendan C.
Abstract : This study investigates the effects of a sulfonated oil (SO) stabilizer on the swell–shrink properties of an expansive soil through cyclic wetting–drying tests. The cyclic wetting–drying action led to the reconstruction of the soil micro-structure by inducing clay particle aggregation. Accordingly, the greater the number of applied cycles, the lower the swell–shrink potential up to the fourth cycle, beyond which the swelling and shrinkage strains attained elastic equilibrium. At any given cycle, the tendency for swell–shrink reduction was in favor of the SO concentration up to 0.75% SO, beyond which the excess SO molecules self-associated in the form of aggregates, thereby acting as a lubricant rather than a clay stabilizing agent. As a result of SO-treatment, the accumulated axial strain progressively transitioned towards a desirable, neutral state, with 0.75% SO exhibiting the highest resistance against cyclic wetting–drying. For any given SO concentration, the equalized void ratio–moisture content curves for wetting and drying followed the same S -shaped path, further corroborating that the swelling and shrinkage processes, upon achieving elastic equilibrium, become reversible. The shrinkage and liquid limits indicated a progressive transition towards a desirable, aggregated fabric, with 0.75% SO identified as the optimum concentration.